Correlation of Cervical Cancer Mortality with Fertility, Access to Health Care and Socioeconomic Indicators - Vale, Diama Bhadra; Sauvaget, Catherine; Murillo, Raul; Muwonge, Richard; Zeferino, Luiz Carlos; Sankaranarayanan, Rengaswamy (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective The present study aimed to examine which development indicators are correlated with cervical cancer (CC) mortality rates in Brazil.Methods This was an ecological study that correlated mortality rates and indicators, such as human development index (HDI), gross domestic product (GDP) per capita, illiteracy rate, fertility rate, screening coverage, proportion of private health insurance use, density of physicians, and density of radiotherapy centers. The mortality rates were obtained from the Brazilian national registry, while the indicators were based on official reports from the Ministry of Health. Univariate and multivariate linear regression was used.Results Among the states of Brazil, the average age-specific CC mortality rate from 2008 to 2012 varied from 4.6 to 22.9 per 100,000 women/year. In the univariate analysis, HDI, proportion of private health insurance use, density of physicians, and density of radiotherapy centers were inversely correlated with the mortality rates. Fertility rate was positively correlated with the mortality rates. In the multivariate analysis, only fertility rate was significantly associated with the CC mortality rate (coefficient of correlation: 9.38; 95% confidence interval [CI]: 5.16–13.59).Conclusion A decrease in the fertility rate, as expected when the level of development of the regions increases, is related to a decrease in the mortality rate of CC. The results of the present study can help to better monitor the quality assessment of CC programs both among and within countries.
Keywords: cervical cancer; cancer mortality; fertility; human development index; health disparities